PERSEPSI PASIEN KELAS III PBI DAN NON-PBI TERHADAP PELAYANAN RAWAT INAP DI RSUD dr. M. YUNUS BENGKULU - Johan; Tjahjono Kuntjoro; Rizaldy Pinzon (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: Management of Public Hospital of dr. M. Yunus continues to strive on improving services quality for their patient, although the result has not been optimal. It demonstrated on achievement of Bed Occupancy Rate (BOR) of the 3rd inpatient class in 2014 still 44,25% (Standard BOR by Health Ministry is 60-85%) means most hospital bed have not utilized and patient number of the 3rd inpatient class showed decreasing from 5.486 in 2013 becomes 3.813 in 2014. Objectives: Identifying perception of the 3rd class patient towards inpatient services in dr. M. Yunus Public Hospital Bengkulu, to know are there differences in perception between insurance contribution and non-insurance contribution. Methods: This study was analytical observational research using cross sectional approach. Number of respondents of this study were 130 patient as beneficiaries of health insurance and 130 patient as non-beneficiaries of health insurance. Sample was determined by proportional random sampling. The analysis used chi square test and qualitative data. Results: Patient perception to quality of service to come cut of paint 25.99 when compared to the cut of point / mean theoretical 25 is categorized good results. The relationship between patient perception PBI towards service quality results are statistically significant p < 0.05. OR value of 2:13 means that the patient’s perception PBI towards service quality is better than the 2:13 time patients NonPBI. Patients’ perceptions towards skills of officers of 26.17 when compared to the cut of point/mean theoretical 25 is categorized good results. The relationship between the patient’s perception PBI towards perceptions of skills results are significant p < 0.05. Practically obtained OR value 1.87 means that the patient’s perception towards skills of officers PBI better by 1.87 times compared to patients NonPBI. Conclusion: Perception of the third-class patient PBI and Non- PBI towards third class inpatient services has been good. There is a difference of perceptions between the groups of patients PBI with NonPBI patient groups.